Morphology and function of the semitendinosus muscle-tendon complex after harvesting its tendon for anterior cruciate ligament reconstruction - Nishino, A.; Fukubayashi, T. (Sports injuries and prevention, 2015)
A considerable decrease in knee flexion strength during deep knee flexion is reported after harvesting the semitendinosus (ST) tendon for anterior cruciate ligament (ACL) reconstruction, although the peak knee flexion strength of the ST tendon-harvested limb can eventually recover almost completely. Strength deficits in deep knee flexion may influence athletic performance in sports activities that require more strength at deep knee flexion. Here we describe morphological changes in the ST as a muscle-tendon complex that may affect knee flexion strength after harvesting the ST tendon for ACL reconstruction. In conclusion, deficits in knee-flexion torque at deep knee flexion are associated with the atrophy and shortening of the ST after harvesting the ST tendon for ACL reconstruction. Maintenance of the ST morphology as a muscle-tendon complex is necessary to ensure postoperative recovery of knee-flexion torque at both shallow and deep knee flexion. We propose that patients should undergo ACL reconstructive surgery and postoperative rehabilitation appropriately to enable regeneration of the ST tendon-like structure while maintaining the morphology of the ST.